Implementasi Algoritma Topsis Pada Sistem Rekomendasi Pencarian Lokasi Gym Berbasis Android (Studi Kasus: Kota Malang) - Ignasius Try Sevandri; Ratih Kartika Dewi; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Muscle fitness is an important thing that cannot be separated from people's lives. Gym places are things that are commonly found in several major cities in Indonesia, especially in Malang City. To be able to practice fitness every time, many people register to become members at the gym, even though only occasionally come to the gym when the time is free. Consumers as customers will choose the factors considered to go to the gym. Consideration factors such as price, location, and people's reviews that can be measured through rating are important in finding the right gym. Based on the importance of finding a suitable gym for community needs, a recommendation system for gyms in Malang City is based on native Android, so it can be a consideration for users in choosing a gym in Malang. Researchers develop mobile-based applications due to several considerations, namely, when choosing a gym, there are distance criteria that have Latitude & Longitude data that can be accessed by GPS in the mobile application. This system was developed using the TOPSIS method. TOPSIS method is suitable for use in the development of research because this method has a low complexity of algorithms so that it is suitable to be applied to mobile applications. The results of the study were the percentage value of the functionality of 100%, the validation test of the validation between manual calculations and the calculation system gets a percentage value of 100% and rank consistency testing for addition and reduction of criteria gets a percentage value of 100%.